Comparative larval ultramorphology of three endemic Lathrobium (Glyptomerus) species (Coleoptera, Staphylinidae, Paederinae) from the Eastern Alps in Italy - Staniec, Bernard; Bordoni, Arnaldo (Zootaxa, 2022)
The paper describes the mature larvae (L2) of Lathrobium alzonai, L. freyi and L. pacei—endemic, depigmented, apterous and subanophthalmous rove beetles from the Eastern Alps in Italy (Coleoptera: Staphylinidae; Paederine)—belonging to the subgenus Glyptomerus. The larva of Lathrobium pacei Piva, 1994 is described for the first time, whereas the larvae of L. alzonai Capra & Binaghi, 1938 and L. freyi Koch, 1938 are redescribed. Detailed illustrations of their structural features are provided, and diagnostic larval - morphological characters for Lathrobium are proposed. Based on earlier published and new data, morphological comparisons, both intergeneric (between Lathrobium and Tetartopeus) and interspecific (between L. alzonai, L. freyi and L. pacei) within the subtribe Lathrobiina, are made. The principal differences among the genera and species involve particular structures of the head and their measurements. The generic status of Tetartopeus was confirmed. No clear differences in the external morphological structure between the larvae of Glyptomerus and Lathrobium s.str. were noted. The morphological structure of L. alzonai larvae differed significantly from that of the larvae of the other two species. The differences relate mainly to the much larger body size of L. alzonai, the shape of the head with its relatively narrow neck, the details of the mouthparts structure and the distinct elongation of its antennae, maxillary palps, labial palps, some parts of the legs and urogomphi. Distribution of all known Italian glyptomeroid species of the genus Lathrobium is also given.